Work environment, work motivation and organizational culture in influencing teachers’ performance - Niko Sudibjo; Rosdiana Akmal Nasution (Universitas Pendidikan Ganesha, 2020)
One crucial factor in determining the successes of learning in schools is the teachers’ performances. Teacher’s performance not only determines the learning successes but also the achievements of the organizational goals. This study aims to determine the effects of the work environment, work motivation, and organizational culture on the teachers’ performance in the XYZ School. The number of subjects in this study was 82 teachers who taught at the XYZ, both the Primary and Secondary levels. A quantitative approach with the PLS-SEM method, in which the Smart PLS application was implemented to process the data, was used in this study. For the data collection, a survey technique using a questionnaire was selected as a research instrument. The results of the data analysis have shown that the work environment, work motivation, and organizational culture have positive effects on performance.